KEBIJAKAN PERTIMBANGAN HAKIM DALAM KASUS TINDAK PIDANA KORUPSI SECARA BERSAMA-SAMA DAN BERLANJUT (Studi Kasus Putusan Nomor 16/Tipikor/2015/PT.Bdg) - Resdian Wisudya Kharismawan; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2018)
Law enforcement against corruption is very urgent to be realized given the corruption crime has been very expanding in the country of Indonesia and is very harmful to the state and citizens. In the judicial process of corruption crime jointly and continuing under the Decision of the Bandung High Court Number 16 / Tipikor / 2015 / PT.Bdg, the judge's ruling becomes an important matter, which determines a person convicted or not. The law gives freedom to the judge to impose a penalty between the minimum and maximum punishment promulgated in the relevant criminal article, in accordance with the provisions of Article 12 of the Criminal Code. However, the point of departure of the judge to impose a conviction is based on the judge's consideration of the threat mentioned in the indicted criminal article. This is the main issue of this research, which is about how the judges judge's judgment policy in the case of corruption crime jointly and continues based on the Decision of the Bandung High Court Number 16 / Tipikor / 2015 / PT.Bdg, and how is the judge's judgment policy should be in the case of a criminal act of corruption jointly and continuously. The method of approach used in this study is empirical juridical, the conclusion of this research is in the criminal imposition of the defendant is still too light compared with criminal sanctions in the legislation and social considerations of the impact of the actions of the defendant, should in case of criminal acts of corruption together and continuing that is related to the provision of Article 10 of the Criminal Code then Criminal in Corruption Criminal can be subject to principal criminal sanction in the form of imprisonment and criminal penalty, and also additional criminal that is deprivation from his position, deprivation of his property if the defendant can not prove that the treasure is not the result of the criminal act of corruption and also as the judge's decision to impose additional additional penalty beyond those provided in the Corruption Act.Key Words :Judge consideration policy based on High Court of Bandung Decision Number 16 / Tipikor / 2015 / PT.Bdg